The effectiveness of marketing strategies on sales of Agromas FAMA consumer products in Melaka / Norfairus Tarudin - Tarudin, Norfairus (Faculty of Business and Management, 2006)
The research is carried out to find out the effectiveness of marketing strategies on sales of Agromas FAMA consumer products in Melaka. The objectives of the study are firstly, to examine the influences of product quality towards the sales of Agromas consumer products, secondly to investigate the impact of distribution channel towards sales of Agromas consumer products and thirdly to identify the types of marketing communications activities that can improve sales of Agromas consumer products. The scope of the study is limited to retailers, agents, wholesalers and 'co-op's of Agromas Melaka. There are 40 of respondents that involved in this study and these studies are using self administration methods collected data. The questionnaire was in dwi-version in order to give respondents easier to answer the question given. The questionnaire was divided into 5 part, which Section A, Section B, Section C, Section 0 and Section E. All the data was analyzed by using the Statistical Package for Social Science (SPSS) version 11.5. Based on the Analyzed data, the results showed that, majority of the respondents were agree with the factors in the marketing strategies like product quality, distribution channel and marketing communications can influence the sales of Agromas consumer products. Meanwhile, hypothesis 1 (There is no correlation between product quality and sales of Agromas consumer product), hypothesis 2 (There is a correlation between distribution channel and sales of Agromas consumer product) and hypothesis 3 (There is a correlation between marketing communications and sales of Agromas consumer product). It means that marketing strategies like distribution channel and marketing communications is effective towards sales of Agromas consumer products. Overall conclusion are: Chapter One, consists of Introduction to the Research, Background of the Study, Problem Statement, Research Question, Research Objective,Theoritical Framework, Hypothesis, Scope of the Study, Limitation of Study Significance of Study and Definition of Terms. Chapter Two is the literature review where the topics and matters concerned are explained in the marketing strategies. The explanation is related the research. Chapter Three is the explanation on Research Methodology. This chapter consists of Introduction, Population of the Study, Sampling, Sampling Frame, Sampling Size, Data Collection Method, Method and Technique, PreTesting and Data Analysis and Interpretation. Chapter Four is Research Findings and Analysis on objectives. Meanwhile Chapter Five contains the Conclusions and Recommendations given by the researcher. Appendices and Bibliography attached are the relevant references like sample of questionnaire, list of respondents, output SPSS and list of books, journals and references that relevant to this research.